Pengaruh Permainan Balok Angka Terhadap Kemampuan Mengenal Lambang Bilangan Pada Anak Usia Dini - Rusmayadi; Rika Kurnia R; Sri Rika Amriani.H; Nursyamsih (ECEJ : Early Childhood Education Journal, 2023)
This research is a quasi-experimental study that aims to determine the effect of the number block game on the ability to recognize number symbols in Early Childhood Kindergarten of Nur Ichsan before and after being given treatment and to find out whether or not the number block effect has on the ability to recognize the symbols of group A children in Early Childhood Kindergarten of Nur Ichsan. This research, the Number Block Game as independent variable, and the ability to recognize number symbols as dependent variable. The population in this study were students at Early Childhood Kindergarten of Nur Ichsan, Takalar Regency, totaling 25 children. Sampling in this study uses purposive sampling. The sample in this study was ten children divided into five children as the experimental group and five as the control group. The data analysis technique used is descriptive statistical analysis and non-parametric analysis. Data analysis results obtained by Asym (2-tailed) = 0.034 <0.05 H1 is accepted, and H0 is rejected, meaning that the ability to recognize number symbols in the experimental class is better than the control class. That proves that the Number Block Game significantly influences the ability to recognize symbols in early childhood numbers.